2021
DOI: 10.1073/pnas.2026461118
|View full text |Cite
|
Sign up to set email alerts
|

Local induction of bladder Th1 responses to combat urinary tract infections

Abstract: Given the high frequency of urinary tract infections (UTIs) and their recurrence, there is keen interest in developing effective UTI vaccines. Currently, most vaccine studies, including those in humans, involve parenteral vaccination aimed at evoking and sustaining elevated levels of systemic antibody directed at the uropathogens. In view of recent reports of aberrant Th2-biased bladder immune responses to infection, we hypothesized that immunizing mice intravesically with antigens from uropathogenic Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 61 publications
(122 reference statements)
0
20
0
Order By: Relevance
“…The immune response of T cells was heavily skewed toward Th2 immune responses during other diseases. [ 14 ] However, the role of T cells in the IC/BPS was largely unknown. We first explored the intrinsic structure and functional subtypes of the T/NK cell populations (Figure S3A , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The immune response of T cells was heavily skewed toward Th2 immune responses during other diseases. [ 14 ] However, the role of T cells in the IC/BPS was largely unknown. We first explored the intrinsic structure and functional subtypes of the T/NK cell populations (Figure S3A , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient antigen uptake from the bladder to nearby lymph nodes would also affect antigen presentation and subsequent activation of adaptive immune cells. As increased bladder damage has been reported to lead to a stronger response (30,37), we reasoned that administering a second UPEC inoculation, as performed in previous studies (15,38,39), might enhance antigen uptake and presentation. The modest GC B cell responses could theoretically also be the result of adaptive immune suppression via cytokines, which is a widely cited reason for a lack of a strong adaptive response in the bladder (8,(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 98%
“…These observations are supported by the results of a study that showed that bladder infection triggers a robust T H 2 cell response, causing re-epithelialization with a limited capacity to clear infection 255 . Furthermore, immunization with UPEC antigens combined with the T H 1-skewing adjuvant CpG was observed to protect mice from developing both single-episode and recurrent UTIs compared with untreated mice 256 . Intravesical vaccination provided a substantially better response than subcutaneous vaccination and was accompanied by an increase in local T H 1 cells.…”
Section: Vaccination Strategiesmentioning
confidence: 97%